Potency and Ecological Habitat of Tabat Barito (Ficus deltoidea Jack) in Natural Forest, South Kalimantan - Yudi Firmanul Arifin; Gusti Muhammad Hatta (Center for Journal Management and Publication, 2015)
Indonesia is rich of medicinal plants, one of which is Tabat Barito (Ficusdeltoidea Jack). The utilization oftabat barito is mainly for women's health and until now its use continues to increase, especially fortraditional medicines, but efforts for cultivation have not been much done. The first step for cultivation is tounderstand the potential and ecological habitat of this plant. This research was conducted in SouthKalimantan, with three villages as the object based on a survey conducted earlier, i.e. the Village of Hamakin Hulu Sungai Selatan District and the Village of Auh and Sungsum in Balangan District. Data wascollected using a survey method to create a transect in the areas where Tabat Barito isfound. The resultsshowed Tabat Barito potential in the two districts is quite rare, between 35 -50 clumps/ha. Tabat Barito wasfound in open areas in natural forest with elevation of 200-350 m above sea level, humidity of 36-54%, airtemperature of 38-43 Â°C, soil temperature of 25 oC. vegetation found to be associated with Tabat Barito inHamak Village is sasirihan (Ficussp.) and beringin (Ficusbenyamina), while in Auh and Sangsum Village ismali-mali (Leeaindica), beringin (F. benyamina), and jambun (Eugenia sp.). The genus of Ficus is thedominant vegetation and significant association with Tabat Barito. The diversity of vegetation, in the HamakVillage is 1.63 higher than Auh and Sungsum Village of 1.16. The common species found in the two districtsthat have Tabat Barito of 28.57%.